Penerapan Model Kooperatif Tipe Jigsaw terhadap Peningkatan Keaktifan Belajar Matematika - Abdul Wahab . A; Suhartini Suhartini; Buhaerah Buhaerah (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2022)
Abstract This study aims to determine whether there is an increase in students' active mathematics learning in class XI MA DDI Lil Banat Parepare using the jigsaw-type cooperative learning model. The type of approach in this research is quantitative, involving students as research subjects. The research was conducted in class XI MIPA MA DDI Lil Banat Parepare with a total of 22 students. Researchers conducted conventional learning in cycle I, then applied the jigsaw-type cooperative learning model in cycle II. The instrument used is an observation sheet with 15 indicators of learning activity. The method used to analyze the data is descriptive quantitative by using the mean and percentage formulas. The results showed the percentage of students' activeness in learning mathematics in jigsaw cooperative learning, namely students paid more attention to the teacher's explanations and were more enthusiastic about participating in learning with a value of 91% in the very good category, while in the conventional learning process the presentation scores were obtained from students who paid attention to the teacher's explanation and enthusiastic in learning that is 82% good category. The conclusion of the study showed that the active learning of mathematics students in class XI MIPA MA DDI Lil Banat Parepare in the conventional learning process obtained an average value of 80.61 with a good category. Then in the learning process using the jigsaw type cooperative model, the average value of the students' mathematics learning activity increased to 88,79 in the very good category. Keywords: Jigsaw cooperative type, active learning, mathematics